2019
DOI: 10.1002/cctc.201901640
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Active Species in a [(R‐SN(H)S‐R)CrCl3] Ethene Trimerization System: Mononuclear or Dinuclear?

Abstract: Cr-catalyzed ethene trimerization is an industrially important process to produce 1-hexene. Despite its industrial relevance, the changing oxidation state and the structural rearrangements of the metal center during the catalytic cycle remain unclear. In this study, we have investigated the active species in a [(R-SN (H)SÀ R)CrCl 3 ] (R = C 10 H 21 ) catalyzed ethene trimerization system using a combination of spectroscopic techniques (XAS, EPR and UV/VIS) and DFT calculations. Reaction of the octahedral Cr II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
0
15
0
1
Order By: Relevance
“…[ 27,108,109 ] The role of Al activators on catalytic performance of chromium catalysts in homogeneous ethylene oligomerization has been recently studied by Tromp, Brückner and co‐workers. [ 110,111 ] With regards to product distribution within the liquid fraction, Cr3 /PMAO‐IP catalytic system leads to a more balanced distribution of oligomers, with a drastic decreases in α‐C 4 (30.20 mol %) and increase in α‐C 8 (16.80 mol %) and α‐C 10 (10.80 mol %) fractions (Figures S9 and S10).…”
Section: Resultsmentioning
confidence: 99%
“…[ 27,108,109 ] The role of Al activators on catalytic performance of chromium catalysts in homogeneous ethylene oligomerization has been recently studied by Tromp, Brückner and co‐workers. [ 110,111 ] With regards to product distribution within the liquid fraction, Cr3 /PMAO‐IP catalytic system leads to a more balanced distribution of oligomers, with a drastic decreases in α‐C 4 (30.20 mol %) and increase in α‐C 8 (16.80 mol %) and α‐C 10 (10.80 mol %) fractions (Figures S9 and S10).…”
Section: Resultsmentioning
confidence: 99%
“…[72] Recently, Tromp used Cr K-Edge XAS and EPR experiments combined with DFT calculations to propose Cr II species as the active species in the trimerization of ethylene. [73,74] Square planar Cr II complexes were observed after activation with MMAO (400eq.) in two different cases (Scheme 30).…”
Section: Chromiummentioning
confidence: 99%
“…In a previous study, we have shown for the [(R-SN(H)S-R)CrCl 3 ] trimerization system, that coordination of the first ethene molecule is endergonic under 1 bar of ethene pressure. 27 Coordination of substrates could be achieved by using more electron-rich substrates (e.g. alkynes).…”
Section: Coordination Of Substrates To the Metalmentioning
confidence: 99%